Downregulation of STEAP4, a highly-expressed TNF-α-inducible gene in adipose tissue, is associated with obesity in humans - Zhang Chun-mei; Chi Xia; Wang Bin; Zhang Min; Ni Yu-hui; Chen Rong-hua; Li Xiao-nan; Guo Xi-rong (Acta Pharmacologica Sinica; Vol 29, No 5 (May 2008): Acta Pharmacologica Sinica, 2016)
Aim: To determine the relationship between six-transmembrane epithelial antigen of the prostate 4 (STEAP4) expression and obesity. Methods: RT–PCR and immunoblot analyses were performed to determine the differential expressions of STEAP4 mRNA and protein, respectively, in human omental adipose tissue from obese patients and normal weight controls. The expression pattern of STEAP4 mRNA in various human tissues was determined by RT–PCR. The subcellular localization of the STEAP4 protein in human adipose tissue was confirmed by immunohistochemistry. Finally, we confirmed that cultured human omental adipose tissue undergoes TNF-α-mediated regulation of the STEAP4 expression. Results: STEAP4 mRNA and protein levels were downregulated in omental adipose tissue from obese patients relative to normal controls. The STEAP4 expression was most abundant in human adipose tissue. An immunohistochemical analysis confirmed that STEAP4 was associated with the plasma membrane of adipocytes. The STEAP4 expression was induced by TNF-α in a dose-dependent manner in human adipose tissue. Conclusion: STEAP4 was abundantly expressed in human adipose tissue, and the STEAP4 expression was significantly downregulated in obese patients. STEAP4 localized to the plasma membrane of adipocytes, and the STEAP4 expression was induced by TNF-α in adipose tissue. These data suggest that STEAP4 may play a significant role in the development of human obesity.